2019
DOI: 10.1002/pc.25381
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbon nanotube/polymer interfacial bonding on the long‐term creep performance of nanophased glass fiber/epoxy composites

Abstract: This article is focused on prediction of the long‐term creep performance of glass fiber/epoxy (GE) composites reinforced with pristine carbon nanotube (CNT) and functionalized carbon nanotube (FCNT). 0.1 wt% of CNT and FCNT are added to GE composites to fabricate CNT‐GE and FCNT‐GE composite laminates, respectively. Flexural tests were carried out at room temperature (RT) and 120°C to assess the effect of environment temperature on the flexural properties of the aforesaid materials. FCNT‐GE showed highest impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 81 publications
(95 reference statements)
0
34
0
Order By: Relevance
“…The chemical bonding between FCNT and epoxy (ester bonds with the epoxide groups) further helps retain it's improved ILSS properties. [54][55][56] In stark contrast, neat CE composites have weak van der Waals interactions between the fiber and matrix. 57,58 Consequently, the load-carrying capacity of the composites is enhanced by improving the efficiency of load transfer across the interface in the case of FCNT-CE composite than neat CE composite.…”
Section: Surface Morphology Of Deposited Fibersmentioning
confidence: 99%
“…The chemical bonding between FCNT and epoxy (ester bonds with the epoxide groups) further helps retain it's improved ILSS properties. [54][55][56] In stark contrast, neat CE composites have weak van der Waals interactions between the fiber and matrix. 57,58 Consequently, the load-carrying capacity of the composites is enhanced by improving the efficiency of load transfer across the interface in the case of FCNT-CE composite than neat CE composite.…”
Section: Surface Morphology Of Deposited Fibersmentioning
confidence: 99%
“…Jia et al 122 found that the formation of CNT network structure can efficiently reduce the creep strain, for CNT/polystyrene nanocomposites. Fulmali et al 123 showed that the weak CNT-polymer bonding can cause slippage during the long-term creep behavior, based on the investigation on CNT/epoxy composites.…”
Section: Creep Performancementioning
confidence: 99%
“…Several studies have shown that the creep behavior of PBMs depends on many factors such as matrix content [ 6 , 7 , 8 , 9 ], particle size [ 10 , 11 , 12 ], stress [ 13 , 14 , 15 ], temperature [ 16 , 17 ], and humidity [ 18 , 19 ]. The importance of long-term properties for polymer composites are highlighted in recent studies [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%